Dismembering the Issues of Capitalism, Human Rights, and Mental Health of Irish People in the Novel Normal People by Sally Rooney - Ferdinal, Ferdinal; Sudarmoko, Sudarmoko; Dewi, Chintya; Oktavianus, Oktavianus (OKARA: Jurnal Bahasa dan Sastra, 2025)
The capitalist ideology has been critiqued in various disciplines, including literature, especially when executed by tyrant governments or influential individuals. This article examines how modern discourse, such as the novel Normal People by Sally Rooney, represents issues of capitalism in Ireland, which impact the rights of its people and their access to mental health. The study is a qualitative scrutiny of the novel, applying the Marxist Theory of Ideology by Louis Althusser to investigate such representations. The primary data from the novel and the secondary information from other sources are interpreted to investigate three main questions: How do Normal People portray capitalism in Ireland, how does this ideology impact the individual rights of its people, and how does it affect access to mental health problems? The study results indicate that the novel portrays the pervasiveness of capitalist ideology in the hearts of Irish people, affecting their rights to live and the freedom of expression, and the practice of capitalism has a substantial impact on Irish youngsters’ mental health. Due to the limitations of the methods and data comprehensiveness, further studies on Normal People may consider alternative literary lenses, such as pragmatic and other analytical approaches, looking at sociocultural institutions and systems.